The differential usage of molecular machinery in brain cancer patients with iron-enriched glioma environments - Brandon Lucke-Wold; Michael Joseph Diaz; Joanna Song; Sai Batchu; Kevin Root; Karan Patel; Kamil Taneja (Journal of Surgery and Surgical Research - Peertechz Publications, 2022)
Gliomas are neuroepithelial tumors in the brain or spinal cord that arise from glial or precursor cells and include astrocytomas, oligodendrogliomas, and ependymomas. They are the most common malignant primary central nervous system tumors, representing 75% of cases in adults and 24% of all cases of primary brain and CNS tumors [1,2]. Despite radiotherapy and temozolomide chemotherapy, which are the current gold-standard first-line treatments, patients with gliomas, particularly the highly aggressive and most common subtype glioblastoma multiforme, still have a poor prognosis with a median survival time of 15 months and 5-year survival rates of 5% [3-6].